Non‐Ultrawide Bandgap Semiconductor GaSe Nanobelts for Sensitive Deep Ultraviolet Light Photodetector Application. Issue 24 (13th May 2022) - Wu, Chun‐Yan; Wang, Ming; Li, Jingyue; Le, Yuxuan; Fei, Wu; Hu, Ji‐Gang; Wu, Di; Zhou, Yu‐Xue; Luo, Lin‐Bao
Abstract: In this paper, the authors report the fabrication of a sensitive deep ultraviolet (DUV) photodetector by using an individual GaSe nanobelt with a thickness of 52.1 nm, which presents the highest photoresponse at 265 nm illumination with a responsivity and photoconductive gain of about 663 A W −1 and 3103 at a 3 V bias, respectively, comparable to or even better than other reported devices based on conventional wide bandgap semiconductors. According to the simulation, this photoelectric property is associated with the wavelength‐dependent absorption coefficient of the GaSe crystal, for which incident light with shorter wavelengths will be absorbed near the surface, while light with longer wavelengths will have a larger penetration depth, leading to a blueshift of the absorption edge with decreasing thickness. Further finite element method (FEM) simulation reveals that the relatively thin GaSe nanobelt exhibits an enhanced transversal standing wave pattern compared to its thicker counterpart at a wavelength of 265 nm, leading to an enhanced light–matter interaction and thereby more efficient photocurrent generation. The device can also function as an effective image sensor with acceptable spatial resolution. This work will shed light on the facile fabrication of a high‐performance DUV photodetector from non‐ultrawide bandgap semiconductors. Abstract : A deep ultraviolet (DUV) photodetector based on an ultrathin non‐ultrawide bandgap semiconductor GaSe nanobelt is fabricated. The blueshift of peak response with decreasing thickness is ascribed to the wavelength‐dependent absorption coefficient of GaSe as well as the enhanced light–matter interaction arising from the longitudinal Fabry–Pérot (F–P) cavity resonance.